Enhanced osteogenesis of human urine-derived stem cells by direct delivery of 30Kc19α–Lin28A protein - Park, Jinhee; Jeong, Kiho; Kim, Manho; Kim, Wijin; Park, Ju Hyun (Frontiers in Bioengineering and Biotechnology, 2023)
Urine-derived stem cells (USCs) are a promising source for regenerative medicine because of their advantages such as easy and non-invasive collection from the human body, stable expansion, and the potential to differentiate into multiple lineages, including osteoblasts. In this study, we propose a strategy to enhance the osteogenic potential of human USCs using Lin28A, a transcription factor that inhibits let-7 miRNA processing. To address concerns regarding the safety of foreign gene integration and potential risk of tumorigenicity, we intracellularly delivered Lin28A as a recombinant protein fused with a cell-penetrating and protein-stabilizing protein, 30Kc19α. 30Kc19α–Lin28A fusion protein exhibited improved thermal stability and was delivered into USCs without significant cytotoxicity. 30Kc19α–Lin28A treatment elevated calcium deposition and upregulated several osteoblast-specific gene expressions in USCs derived from multiple donors. Our results indicate that intracellularly delivered 30Kc19α–Lin28A enhances the osteoblastic differentiation of human USCs by affecting the transcriptional regulatory network involved in metabolic reprogramming and stem cell potency. Therefore, 30Kc19α–Lin28A may provide a technical advancement toward developing clinically feasible strategies for bone regeneration.